Monitoring Atmospheric, Soil, and Dissolved CO2 Using a Low-Cost, Arduino Monitoring Platform (CO2-LAMP): Theory, Fabrication, and Operation - Blackstock, Joshua M.; Covington, Matthew D.; Perne, Matija; Myre, Joseph M. (Frontiers in Earth Science, 2019)
Variability of CO2 concentrations within the Earth system occurs over a wide range of time and spatial scales. Resolving this variability and its drivers in terrestrial and aquatic environments ultimately requires high-resolution spatial and temporal monitoring; however, relatively high-cost gas analyzers and data loggers can present barriers in terms of cost and functionality. To overcome these barriers, we developed a low-cost Arduino monitoring platform (CO2-LAMP) for recording CO2 variability in electronically harsh conditions: humid air, soil, and aquatic environments. A relatively inexpensive CO2 gas analyzer was waterproofed using a semi-permeable, expanded polytetrafluoroethylene membrane. Using first principles, we derived a formulation of the theoretical operation and measurement of PCO2(aq) by infrared gas analyzers submerged in aquatic environments. This analysis revealed that an IRGA should be able to measure PCO2(aq) independent of corrections for hydrostatic pressure. CO2-LAMP theoretical operation and measurement were also verified by accompanying laboratory assessment measuring PCO2(aq) at multiple water depths. The monitoring platform was also deployed at two sites within the Springfield Plateau province in northwest Arkansas, USA: Blowing Springs Cave and the Savoy Experimental Watershed. At Blowing Springs Cave, the CO2-LAMP operated alongside a relatively greater-cost CO2 monitoring platform. Over the monitoring period, measured values between the two systems covaried linearly (r2 = 0.97 and 0.99 for cave air and cave stream dissolved CO2, respectively). At the Savoy Experimental Watershed, measured soil CO2 variability capturing sub-daily variation was consistent with previously documented studies in humid, temperate soils. Daily median values varied linearly with soil moisture content (r2 = 0.84). Overall, the CO2-LAMP captured sub-daily variability of CO2 in humid air, soil, and aquatic environments that, while out of the scope of the study, highlight both cyclical and complex CO2 behavior. At present, long-term assessment of platform design is ongoing. Considering cost-savings, CO2-LAMP presents a working base design for continuous, accurate, low-power, and low-cost CO2 monitoring for remote locations.